The shape of the Roman order : the republic and its spaces - Gargola, Daniel J. (Chapel Hill : The University of North Carolina Press, 2017)
"Rather than trying to understand the [Roman] Empire through the lens of modern organizations and institutions, Gargola looks at the idiosyncratic way the elite viewed the geographical world around them and how it fundamentally informed the way they ruled over their dominion. From what geometrical patterns they preferred to how they constructed their hierarchies in space, Gargola brings together a wide body of disparate materials to demonstrate how spatial orientation dictated action"--
Representing the res publica -- Rome, its magistrates, and its empire -- Rome and its Italy -- The augurs and their spaces -- Sciences of the center -- Laws, decrees, edicts, and their spaces.
Includes bibliographical references (pages 231-286) and index.
Keywords: Space perception -- Rome -- History; Public spaces -- Rome -- History; Politics and government; Public spaces; Space perception; Rome -- Politics and government; Rome (Empire); History